Why "Bologna" in the library and information studies? - Moreiro, José Antonio (Anuario ThinkEPI, 2010)
Reflection on the benefits to Spanish universities of the Bologna process for standardizing European university studies. Considered factors are: globalization, European integration, labour market needs, and changes in training due to the new technologies.